Do HIV treatment eligibility expansions crowd out the sickest?: Evidence from rural South Africa - Kluberg, Sheryl; Bärnighausen, Till (Tropical medicine & international health, 2018)
The 2015 WHO recommendation to initiate all HIV patients on antiretroviral therapy (ART) at diagnosis could potentially overextend health systems and crowd out sicker patients, mitigating the policy's impact. We evaluate whether South Africa's prior eligibility expansion from CD4 ≤ 200 to CD4 ≤ 350 cells/μl reduced ART uptake in the sickest patients.
Gesehen am 18.11.2019